Response of sesame varieties to phosphorus fertilisation and phosphobacteria inoculation: Effects on nutrient uptake, availability, use efficiency and yield of sesame - Kamalakannan, P; Sureka, K; Arivukkarasu, K; Lenin, A R; Shankari, A (Plant Science Today, 2026)
A field experiment was conducted at a farmers’ field from April to August 2021 in Korakottai Village, Vandavasi Taluk, Tiruvannamalai District, to evaluate the effects of phosphorus fertilisation and phosphobacteria inoculation on nutrient uptake, availability, use efficiency and productivity of sesame varieties (TMV 3 and ASWIN 3). The study followed a factorial randomised block design with six phosphorus levels, viz., Control, 25 % RDP, 50 % RDP, 75 % RDP, 100 % RDP and 125 % RDP and two levels of phosphobacteria application, viz., control and phosphobacteria at 2 kg ha-1, replicated thrice. The results revealed that both individual and combined applications of 100 % recommended phosphorus dose along with phosphobacteria at 2 kg ha-1 significantly enhanced nitrogen, phosphorus and potassium uptake and availability, phosphobacteria population, response ratio and apparent recovery, as well as seed and stalk yields in both varieties. Considering these benefits, the application of 100 % recommended phosphorus dose along with phosphobacteria at 2 kg ha-1 is recommended for sesame farmers in Tiruvannamalai district, Tamil Nadu, to achieve higher yields and profitability.